Sosialisasi Tehnik Distraksi dan Relaksasi Sebagai Upaya Menurunkan Tingkat Kecemasan Ibu Saat Menghadapi Proses Persalinan - Suci Anggraeni; Reni Yuli Astutik; Nining Istighosah (JOURNAL OF PHILANTHROPY: The Journal of Community Service, 2023)
Pregnancy is something that naturally occurs in productive women. During each pregnancy, the mother will experience several changes, both physical changes and psychological changes that are quite specific as a reaction to what she feels during pregnancy. So it does not rule out the possibility for a pregnant woman, especially the final third trimester who will face the labor process, tends to experience anxiety. Distraction and relaxation techniques are non-pharmacological interventions that can be applied to pregnant women in labor. This technique is very useful for reducing or eliminating anxiety when facing labor. The purpose of this community service activity is to provide knowledge and train pregnant women about distraction and relaxation techniques to reduce anxiety levels in dealing with the delivery process. The target of this community service activity is 15 pregnant women. The activity consists of three stages, namely the preparation, implementation, and evaluation stages. The activity begins with a pre test to measure the level of knowledge of respondents using a questionnaire, followed by education and simulation and ends with a post test. The results of the post test showed that 80% of the respondents had good knowledge and 20% had sufficient knowledge. Community service activities through education and demonstrations about distraction and relaxation techniques to reduce anxiety levels in dealing with the delivery process can increase pregnant women's knowledge.